Early Challenges: A Case Report of a Premature Baby with Down Syndrome and Uterine Rupture - Jerbi, Bilel; Chourou, Hajer; Ben Aziza, Rim; Belhadj Ammar, Wafa; Kacem, Samia; Achour, Radhouane (American Journal of Perinatology Reports, 2024)
Introduction Uterine rupture represents one of the most severe obstetric affections. It is defined as a complete or a partial tearing of the uterine wall. Women with a prior cesarean section are reported to have a higher risk of having this situation. Moreover, maternal death and most of all middle- and long-term adverse consequences remain a great preoccupation. On another scale, neonatal death and ulterior deterioration remain very high, especially in low-income countries.Case Description A 24-year-old woman with a history of previous cesarean section presented at 35 weeks of gestation with pelvic pain without bleeding. Emergency cesarean section revealed a complete uterine rupture at the scar site from the previous cesarean section. Remarkably, the fetus managed to seal the rupture using the right temporal region, forearm, and right leg, avoiding significant complications. The mother had an uncomplicated postoperative course and was discharged after 48 hours of surveillance.Conclusion We present with this case an extraordinary case of a uterine rupture where both mother and child had a good outcome. This rare evolution was reported only one time in literature. For this reason, a history of caesarean delivery might present a huge challenge for obstetricians and neonates.
Keywords: cesarean Section; diagnosis; perinatal morbidity; uterine rupture; scarred uterine rupture